2003
DOI: 10.1590/s1516-14392003000300004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characterisation of porous glass reinforced hydroxyapatite ceramics: Bonelike®

Abstract: In the present study, mechanical properties of porous glass reinforced hydroxyapatite bioceramics were assessed by microhardness, bending and compression tests and fracture toughness determination. Porous discs were produced by a dry method using wax spheres as pore formers. Green bodies were sintered and the final microstructure of the composites consists of hydroxyapatite, alpha and beta tricalcium phosphate (alpha and b-Ca3(PO4)2)due to the reaction between the glassy phase and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
(11 reference statements)
2
6
0
Order By: Relevance
“…The compressive data reported is comparable to that of dense HA-BG hybrids [455,496]. Previous work has also sought to combine HA with phosphate-based glass, and the compressive strength and porosity thereof are comparable to that obtained herein [497,498]. Similarly, BG has been combined with other bioceramics, such as β-TCP and calcium sulphate, which have attained compressive strengths below that obtained in this study [290,499,500].…”
Section: The Resultant Compressive Strength and Comparison To Other Ssupporting
confidence: 74%
See 1 more Smart Citation
“…The compressive data reported is comparable to that of dense HA-BG hybrids [455,496]. Previous work has also sought to combine HA with phosphate-based glass, and the compressive strength and porosity thereof are comparable to that obtained herein [497,498]. Similarly, BG has been combined with other bioceramics, such as β-TCP and calcium sulphate, which have attained compressive strengths below that obtained in this study [290,499,500].…”
Section: The Resultant Compressive Strength and Comparison To Other Ssupporting
confidence: 74%
“…Bonelike®, which has been stated as a promising material with enhanced bioactivity compared to HA-only material [149,502], and is suitable for direct clinical use, consists of HA with 4 wt% bioactive glass. Though the porosity values are comparable to that of the samples examined in the present study, the compressive strengths and macro-pore sizes are, respectively, 2 MPa and 100 µm [498]. Hence, the hybrid scaffolds fabricated herein, comprised of a higher glass content, remarkably greater compressive strength and larger pore sizes, would be more desirable for BGS.…”
Section: The Resultant Compressive Strength and Comparison To Other Ssupporting
confidence: 56%
“…This was confirmed when Bonelike ® was implanted in the tibia of 13 patients during osteotomy surgery, with the aim of treating the medial compartment osteoarthritis of the knee . Although the porosity values are similar, hitherto the compressive strengths reported for Bonelike ® are 2 MPa with pore sizes of approximately 100 μm . Therefore, comprised of a higher glass composition and remarkably greater compressive strengths, it can be concluded that honeycomb extruded hybrid scaffolds used for similar clinical applications will result in superior biological and mechanical performances.…”
Section: Resultsmentioning
confidence: 78%
“…The average maximum indentation depths obtained at the end of the measurement are shown in Table 5, while the Vickers hardness and elasticity modulus values are given in Table 6. When the data in Table 5 are examined, it can be observed that the average indentation depths (ht) at maximum load increase continuously with the increase in holding period (24,48 , 72 and 96 h).…”
Section: Ultra Microhardness (Indentation) Testsmentioning
confidence: 99%
“…The fracture toughness values obtained are shown in Table 8. In the literature, when the calculated fracture toughness values of the HA coating surfaces were examined, the fracture toughness values of hydroxyapatite coating surfaces made by Zhang [24], between 0.23 and 1.20 MPa m 1/2 [25], between 0.49 and 0.67 MPa m 1/2 [26], between 0.99 and 1.27 MPa m 1/2 value [27] and 0.74 MPa m 1/2 , respectively [28]. Çaglayan found the fracture toughness values of coatings obtained in the Alanine-Alanine sodium salt buffer medium as 1.57 MPa m 1/2 , 1.73 MPa m 1/2 , 2.29 MPa m 1/2 and 2.31 MPa m 1 for 24, 48, 72 and 96 h, respectively [22].…”
Section: Fracture Toughnessmentioning
confidence: 99%